The Prevalence and Diagnostic Utility of Systemic Inflammatory Response Syndrome Vital Signs in a Pediatric Emergency Department. (16th March 2015) - Scott, Halden F.; Deakyne, Sara J.; Woods, Jason M.; Bajaj, Lalit; Macy, Michelle L.
Abstract Objectives This study sought to determine the prevalence, test characteristics, and severity of illness of pediatric patients with systemic inflammatory response syndrome (SIRS) vital signs among pediatric emergency department (ED) visits. Methods This was a retrospective descriptive cohort study of all visits to the ED of a tertiary academic free‐standing pediatric hospital over 1 year. Visits were included if the patient was <18 years of age and did not leave before full evaluation or against medical advice. Exclusion criteria were trauma diagnoses or missing documentation of vital signs. Data were electronically extracted from the medical record. The primary predictor was presence of vital signs meeting pediatric SIRS definitions. Specific vital sign pairs comprising SIRS were evaluated as predictors (temperature–heart rate, temperature–respiratory rate, and temperature‐corrected heart rate, in which a formula was used to correct heart rate for degree of temperature elevation). The primary outcome measure was requirement for critical care (receipt of a vasoactive agent or intubation) within 24 hours of ED arrival. Results There were 56, 210 visits during the study period; 40, 356 met inclusion criteria. Of these, 6, 596 (16.3%) visits had fever >38.5°C, and 6, 122 (15.2% of included visits) met SIRS vital sign criteria. Among included visits, those with SIRS vital signs accounted for 92.8% of all visits with fever >38.5°C. Among patients with SIRS vital signs, 4993 (81.6%) were discharged from the ED without intravenous (IV) therapy and without 72‐hour readmission. Critical care within the first 24 hours was present in 99 (0.25%) patients: 23 patients with and 76 without SIRS vital signs. Intensive care unit (ICU) admission was present in 126 (2.06%) with SIRS vital signs and 487 (1.42%) without SIRS vital signs. SIRS vital signs were associated with increased risk of critical care within 24 hours (relative risk [RR] = 1.69, 95% confidence interval [CI] = 1.06 to 2.70), ICU admission (RR = 1.45, 95% CI = 1.19 to 1.76), ED laboratory tests (RR = 1.41, 95% CI = 1.37 to 1.45), ED IV medication/fluid administration (RR = 2.54, 95% CI = 2.29 to 2.82), hospital admission (RR = 1.52, 95% CI = 1.42 to 1.63), and 72‐hour readmission (RR = 1.31, 95% CI = 1.01 to 1.69). SIRS vital signs were not associated with 30‐day in‐hospital mortality (RR = 0.37, 95% CI = 0.05 to 2.82). SIRS vital signs had a low sensitivity for critical care requirement (23.2%, 95% CI = 15.3% to 32.8%). The pair of SIRS vital signs with the strongest association with critical care requirement was temperature and corrected heart rate (positive likelihood ratio = 2.74, 95% CI = 1.87 to 4.01). Conclusions Systemic inflammatory response syndrome vital signs are common among medical pediatric patients presenting to an ED, and critical illness is rare. The majority of patients with SIRS vital signs were discharged without IV therapy and without readmission. Patients with SIRS vital signs had a statistically significant increased risk of critical care requirement, ED IV treatment, ED laboratory tests, admission, and readmission. However, SIRS vital sign criteria did not identify the majority of patients with mortality or need for critical care. SIRS vital signs had low sensitivity for critical illness, making it poorly suited for use in isolation in this setting as a test to detect children requiring sepsis resuscitation.